Pregnant women’s awareness of dental care with regard to prophylaxis of oral diseases - Przeklasa, Anna; Jakubik, Anna; Szczeklik, Katarzyna; Pytko-Polończyk, Jolanta (Journal of Stomatology, 2015)
Introduction. The issue of pregnant women’s dental care is broadly discussed in literature. Research shows poor oral health among expectant mothers and a low level of their awareness in this regard. Low availability of preventive actions and insufficient information in this field from medical staff were both confirmed by the results of a questionnaire research amid these women. Aim of the study. To characterize the main dental issues and to evaluate knowledge concerning dental prophylaxis of pregnant women from the Małopolskie province. Materials and methods. A questionnaire study was conducted among 132 women from Cracow and its surroundings. Questions concerned oral hygiene habits, dental problems and possibilities of dental treatment during pregnancy, sources of information in this field. Results were statistically analysed with Statistica v.10.0, using the chi-squared test. The statistical point of significance was set at p<0.05. Results. Women who live in the city, as compared to those living in smaller locations, have a much easier access to campaigns informing about oral health during the pregnancy period. Internet websites were the main source of knowledge (66.7% of respondents), whereas childbirth classes took the last place (3.8% of surveyed women). A relationship between the education of the surveyed women and the level of their dental awareness was demonstrated. More than a half of the respondents (61.4%) claim there is no influence of parent’s oral health on their progeny. Moreover, multiparous women exhibited a far better knowledge of dental proceedings available during pregnancy than the first-time mothers. Conclusions. The reported lack of knowledge concerns oral hygiene habits during pregnancy, procedures available in this period and the influence of parents' oral health on their offspring. It is necessary to educate future mothers on the prophylaxis of oral diseases, both in the form of preventive actions, as well as by an increased attention of their general practitioners, dentists, gynaecologists, focusing on this issue.